2021
DOI: 10.7554/elife.68394
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuned repression of Drp1-driven mitochondrial fission primes a ‘stem/progenitor-like state’ to support neoplastic transformation

Abstract: Gene knockout of the master regulator of mitochondrial fission, Drp1, prevents neoplastic transformation. Also, mitochondrial fission and its opposing process of mitochondrial fusion are emerging as crucial regulators of stemness. Intriguingly, stem/progenitor cells maintaining repressed mitochondrial fission are primed for self-renewal and proliferation. Using our newly derived carcinogen transformed human cell model we demonstrate that fine-tuned Drp1 repression primes a slow cycling 'stem/progenitor-like st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…DRP1 inhibition and mitochondrial fusion inhibit apoptosis induced by a variety of stress situations ( 38, 39, 48, 49 ). Moreover, fine tuning of DRP1 activity to increase mitochondrial fusion and OXPHOS has further been associated with increased oncogenic transformation ( 50, 51 ). LENOX may therefore optimize OXPHOS and survival to favor oncogenic transformation and subsequent progression in stressful cellular environments encountered during primary tumor growth and metastatic dissemination ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…DRP1 inhibition and mitochondrial fusion inhibit apoptosis induced by a variety of stress situations ( 38, 39, 48, 49 ). Moreover, fine tuning of DRP1 activity to increase mitochondrial fusion and OXPHOS has further been associated with increased oncogenic transformation ( 50, 51 ). LENOX may therefore optimize OXPHOS and survival to favor oncogenic transformation and subsequent progression in stressful cellular environments encountered during primary tumor growth and metastatic dissemination ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, Drp1-mediated fission is crucial for mitosis in cancer cells 14, 15 , while on the other hand, fragmented mitochondria hinder the G1-S transition in cells, which is linked to the accumulation of cyclin E and a hyperfused mitochondria 63 . Similarly, elevated mitochondrial fusion has been identified as a feature of ovarian cancer neoplastic stem cells, priming them for self-renewal and proliferation 64 . We predict these conflicting reports related to Drp1 expression and cell proliferation might be partially resolved by considering Drp1 variant expression.…”
Section: Discussionmentioning
confidence: 99%
“…Yet it is known that during G1-S transition, mitochondrial networks fuse, which aids in cyclin E mediated G1-S transition, and inhibition of Drp1-mediated fission can induce the proliferation of quiescent cells 63 . Similarly, elevated mitochondrial fusion has been identified as a feature of ovarian cancer neoplastic stem cells, priming them for self-renewal and proliferation 64 . Our present work suggests distinct impacts of Drp1 alternative splice variants on cell proliferation, and one might speculate that their variable abundance could be associated with changes in cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…14: 230279 royalsocietypublishing.org/journal/rsob Open Biol. 14: 230279 smaller network size (comprising of ≤ 40% of the total mitochondrial network size) supports stem cell gene expression profile in keratinocyte lineage, while almost complete fusion of mitochondrial network (hyperfusion) prevents it [128]. The smaller mitochondrial network size is reminiscent of the theoretical conceptualization of a quantitively defined 'meso-fused' royalsocietypublishing.org/journal/rsob Open Biol.…”
Section: Quantitative Aspects Of Heterogeneity Of Mitochondrial Shape...mentioning
confidence: 96%
“…The majority of such studies investigated the impact of mitochondrial shape at the extremes of the morphometric spectrum, largely leaving out the shapes in between the extremes. Precise quantification of mitochondrial network length revealed that maintenance of smaller network size (comprising of ≤ 40% of the total mitochondrial network size) supports stem cell gene expression profile in keratinocyte lineage, while almost complete fusion of mitochondrial network (hyperfusion) prevents it [ 128 ]. The smaller mitochondrial network size is reminiscent of the theoretical conceptualization of a quantitively defined ‘meso-fused’ mitochondrial structure, where the active fission rate dominates to maintain smaller mitochondrial network size [ 141 ].…”
Section: Quantitative Aspects Of Heterogeneity Of Mitochondrial Shape...mentioning
confidence: 99%